Gastrointestinal Stromal Tumor (GIST) presenting as acute abdomen: Image in surgery - Med Dheker Touati; Marwa Idani; Mohamed Raouf Ben Othmane; Fahd Khefacha; Nadhem Khelifi; Anis Belhadj; Ahmed Saidani; Faouzi Chebbi (Journal of Surgery and Surgical Research - Peertechz Publications, 2023)
Gastrointestinal stromal tumors originating from the small bowel are uncommon. We present the case of a 45-year-old man with no prior medical or surgical history who presented to our hospital's emergency department with abdominal pain, vomiting, inability to pass gas, and no bowel movements. Physical examination revealed abdominal distention and tenderness. His white blood cell count was 10.9 x 10^3/µl, and hemoglobin levels were 13.3 g/dl.